Pandora hearts. 06 - Mochizuki, Jun (Yen Press, 2011)
Uncle Oscar drags Oz and company on a "mission" to Lutwidge Academy, where Oz's little sister, Ada, is a student. But some carefree fun and a tearful reunion ten years in the making is not all for which Oz must prepare himself. Crimson-cloaked foes are lying in wait to torture him for answers about the events of a hundred years ago.